الجهود الدعوية للمرأة المسلمة أمال زواغي _نموذجا - جديعي, رزيقة; زروقي, فتيحة; زكور, جليلة (جامعة الوادي university of eloued, 2019)
نضع بين يديدم ذا بحث با بنوا ) لجهاد لإعلامية بلمرية لمسلمة يمال زو غي نماذجا(، و با تواوبوا فيها بيور لمه با تلنحه لمرية لمسلمة في تحليغ بيعاة إلى لله، وينها و جب عليها كأخيها برجل تماما، حي كا) لهيف لأسمى من ذا بحث ذا إبر ز يذ لأدو ر و لجهاد بتي تحالها لمرية لمسلمة في مجال بيعاة . وبقي يخترنا رمز من رماز ذا لمجال وذي : بي عية يمال زو غي، و بتي كانت محار در ستوا في ذا بحث ، حي حاوبوا تسليط بضاء على يذ يعمالها بيعادة و لإعلامية، وذبك من خلال باقاف على يذ مر حل حياتها بشخصية و باظيفية و بنملية وكا مشاركتها في خيمة بيدن و لمجتمع، وذبلك خلال ببر مج و لأنشطة بتي قامت بها بي عية، و بتي ستطاعت من خلالها ي) تخط بوفسها تاريخا حافلا بالإنجاز ت لمتواعة، فنن ذا تاصلوا من خلال ذاه بير سة إلى ي مي كانت بي عية مثابرة في مهمتها وطردقها رغ مناناة لمرض با يصابها حتي صارت مثلا وقيوة يحتا بها بي بمثير من يخا تها لمسلمات بطماحات لمثل ذا بنمل بوحيل. Abstract: We put in your hands this research entitled: ( Media efforts of Muslim women ), in which we discussed the important role played by Muslim women in reporting the call to Allah almighty, and that it is a duty as her brother the man completely where the ultimate goal of this research is to highlight the most important roles and efforts that by Muslim women in the field of Islam calling we have chosen the symbols of this field namely the preacher *Amal zouaghi* which was the focus of our study in this research, where we tried to highlight the most important work of islam calling and information, and by standing on the most important stage of personal life, functional and practical as well as their participation in the service of religion and society, And through the programs and activities out by the so called preacher, and through which she managed to leap to herself a history of diverse achievements it is through this study, we reached to what extent the perseverance in her mission and way, despite the suffering of the disease that has become a model and example to be followed by many of his sisters muslims aspire to such voble and blessed work.
دعوة